Preservation of library, archival and digital documents : (Ess Ess Publications, 2008)
Preservation is concerned with problems such as repair, dusting, fumigation, deacidification, air-conditioning, lamination, binding, storage, etc. The principles of preservation of documentary materials in libraries, archives, and digital databases in the light of rapid technological advances need to be reexamined and reevaluated. This book consists of 33 papers written by scholars, experts, and practicing librarians. These contributors discuss various preservation problems experienced in their work environments, and they offer practical solutions.